Jahr and Potter : accidental similarities? - Araújo, Antonio Fábio Medrado de (Array, 2020)
With the science of survival article and lately the book “bridge to the future” Potter became famous releasing the neologism “bioethics” and then known as the founder of bioethics. However, 43 years before, Jahr had proposed a similar idea in the article “Bio-ethics: reviewing the ethical relations of humans towards animals and plants (translated from German)”. We propose to correct the idea that Jahr is merely a precursor—and not a founder—of bioethics, here speculating the bridge bioethics of Rensselaer Potter as close similarity with Jahr’s thoughts. Following the “content analysis” method, a table was built to compare the theoretical schemes of Potter and Jahr, correlating by qualitative meta-analysis, each paragraph of Jahr’s base text (1927) with Potter’s analogous (1970). The similarity of the texts reveals that, in theory, Potter benefited from Jahrist utopia, imposing it a reductionist lineage. Potter expresses, therefore, an ethnological capture of jahrism.